The Role of Islamic Religious Education Teachers in Shaping the Character of Elementary School Students - Selina, Nur; Darmayanti; Rusli (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to analyze the crucial role of Islamic Religious Education (PAI) teachers in shaping students’ character and to identify both supporting and inhibiting factors that influence their effectiveness at SD Negeri 3 Wameo, Baubau City. The problem addressed in this study lies in the challenges faced by PAI teachers in developing students’ moral and behavioral character amid varying family and social environments. This research employs a qualitative method with an inductive and descriptive approach to provide an in-depth understanding of how PAI teachers implement character education and how environmental factors affect the process. The findings reveal that PAI teachers play a significant role in guiding students toward positive character formation through exemplary behavior, moral instruction, and continuous mentoring. The supporting factors consist of internal elements such as students’ self-awareness, intrinsic motivation, and family participation, which contribute positively to character development. Conversely, the inhibiting factors include external aspects such as negative social influences and unsupportive peer environments that can weaken the teacher’s efforts in shaping moral values. Overall, the study concludes that the success of character education largely depends on the synergy between teachers, families, and the surrounding social environment.